Combined Histo-endoscopic Remission but not Endoscopic Healing Alone in Ulcerative Colitis is Associated with a Mucosal Transcriptional Profile Resembling Healthy Mucosa. (6th January 2022) - Hernández-Rocha, Cristian; Nayeri, Shadi; Turpin, Williams; Steel, Mike; Borowski, Krzysztof; Stempak, Joanne M; Conner, James; Silverberg, Mark S
Abstract: Background and Aims: A composite endpoint of histological and endoscopic remission is proposed to be the most complete measure of mucosal healing in ulcerative colitis [UC]. We aim to establish the prognosis, and transcriptional and microbial features of histo-endoscopic remission and activity. Methods: A cross-sectional endoscopic rectosigmoid colon sample collection from UC patients and healthy controls [HC] was performed for histopathology and host genome-wide RNA-sequencing. Histo-endoscopic remission and histo-endoscopic activity were defined as Mayo endoscopic subscore [MES] 0–1 with and without histological activity, respectively. UC relapse, defined as symptomatic and endoscopic worsening, was retrospectively recorded for survival analysis. Unsupervised and differential gene expression analyses were performed, and the interaction between transcriptomics and mucosal gut microbiota was analysed based on the 16S rRNA gene sequencing profile. Results: UC patients with histo-endoscopic remission showed a significantly lower risk of relapse compared to histo-endoscopic activity. Unsupervised analysis of the transcriptomic profile showed that histo-endoscopic remission and histo-endoscopic activity samples clustered with HC and MES 2–3 samples, respectively. A total of 452 host genes enriched for humoral immune response, antimicrobial defence, chemokine and TH17 signalling pathway were upregulated in histo-endoscopic activity compared to histo-endoscopic remission. A set of host genes with antimicrobial properties showed significant associations with mucosal microbiota. Conclusions: The rectosigmoid mucosa transcriptional profile of UC patients in histo-endoscopic remission resembles that of HC mucosa and confers a lower risk of relapse. These data support that the combination of histo-endoscopic remission could be the most appropriate definition of mucosal healing in UC.